Mekanisme molekuler ketergantungan terhadap nikotin - silmi., nur. (Maliki Interdisciplinary Journal, 2025)
Nicotine, the main addictive substance of tobacco, plays an important role in the dependence mechanism. Complex interactions between the central and peripheral nervous systems lead to nicotine dependence, primarily due to activation of nicotinic acetylcholine receptors in the brain. Activation of these receptors triggers the release of neurotransmitters, such as dopamine, that make people feel euphoric and calm, which encourages repeated nicotine use behavior. In addition, dopaminergic and glutamatergic signaling pathways undergo molecular changes, resulting in neuroplastic changes and increased tolerance to nicotine. This study focuses on the role of nicotinic acetylcholine receptors, neurotransmitter regulation, and neuroplastic changes in the limbic system. Understanding these mechanisms can help develop better therapeutic methods to overcome nicotine dependence and reduce the adverse effects caused by nicotine consumption.